HUBUNGAN BAURAN PROMOSI, PENDIDIKAN KESEHATAN REPRODUKSI REMAJA DAN PERAN ORANG TUA TERHADAP PEMANFAATAN PELAYANAN KESEHATAN PEDULI REMAJA (PKPR) DI SMK KESEHATAN GEMA NUSANTARA BUKITTINGGI TAHUN 2022 - Patri Sepdiana; Sumihardi (Jurnal Kesehatan dan Pembangunan, 2023)
The purpose of this study was to determine the relationship between promotion mix, adolescent reproductive health education and the role of parents on the utilization of Adolescent Care Health Services (PKPR) at Gema Nusantara Health Vocational School, Bukittinggi and Padang City. The population is 551 students of class XII at SMK Kesehatan Gema Nusantara Bukittinggi and Padang City. The sample of this study used the slovin formula, obtained as many as 85 respondents. The research instrument used a questionnaire. The type of research used in this research is quantitative research with a cross sectional design. The analysis technique used was univariate, bivariate and multivariate. The results showed that there was a positive and significant relationship between promotion mix and adolescent care health services at Gema Nusantara Health Vocational School, Bukittinggi and Padang City. There is a positive and significant relationship between adolescent reproductive health education and adolescent care health services at Gema Nusantara Health Vocational Schools in Bukittinggi and Padang City. There is a positive and significant relationship between the role of parents and health care services for adolescents at Gema Nusantara Health Vocational School in Bukittinggi and Padang City. The promotion mix, adolescent reproductive health education and the role of parents together have a positive and significant relationship with adolescent care health services. From the results of the research above it is recommended to the Gema Nusantara Health Vocational School, Bukittinggi and Padang City to further improve the mix of promotion of adolescent reproductive health education and the role of parents in adolescent care health services.